2022
DOI: 10.1186/s13287-022-02912-1
|View full text |Cite
|
Sign up to set email alerts
|

Research status and future prospects of extracellular vesicles in primary Sjögren’s syndrome

Abstract: Primary Sjögren’s syndrome (pSS) is a diffuse connective tissue disease characterized by the invasion of exocrine glands such as lacrimal and salivary glands, abnormal proliferation of T and B lymphocytes, and infiltration of tissue lymphocytes. With the development of modern medicine, although research on the pathogenesis, diagnosis, and treatment of pSS has made significant progress, its pathogenesis has not been fully understood. Meanwhile, in the era of individualized treatment, it remains essential to fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…pSS is a chronic systemic autoimmune disease characterized by lymphocyte proliferation and progressive exocrine gland damage 22 . Since the onset of dry syndrome is insidious, the clinical manifestations of patients are different, and the severity of the disease also varies greatly, so the early and clear diagnosis of the disease has important clinical significance to improve the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…pSS is a chronic systemic autoimmune disease characterized by lymphocyte proliferation and progressive exocrine gland damage 22 . Since the onset of dry syndrome is insidious, the clinical manifestations of patients are different, and the severity of the disease also varies greatly, so the early and clear diagnosis of the disease has important clinical significance to improve the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In SS patients’ T cells, it was found that exosomes contained a specific miRNA that adversely affects calcium and cAMP pathways, decreasing protein production by salivary epithelial cells. Additionally, exosomes isolated from the tears of SS patients were found to contain more TNF-alpha-related factors and B-cell survival-related proteins [ 130 ].…”
Section: On the Horizon—novel Diagnostic Modalitiesmentioning
confidence: 99%
“…However, MSC administration was found to be limited by donor compatibility and long preparation times of autologous transplants [ 84 ]. In this case, exosomes derived from MSCs have been shown to overcome these difficulties.…”
Section: On the Horizon: Mesenchymal Stem Cells Therapy And Exosomesmentioning
confidence: 99%
“…When transplanted or infused in mice, exosomes derived from MSCs were shown to decrease symptoms of SS and differentiate into different salivary gland cells, resulting in restored function of the glands [ 84 ]. Labial gland derived MSCs and their associated exosomes have been found to rebalance the expression of miRNA-125b-5p and miRNA-155-5p in CD4+ T cells [ 86 , 87 ].…”
Section: On the Horizon: Mesenchymal Stem Cells Therapy And Exosomesmentioning
confidence: 99%
See 1 more Smart Citation